2020
DOI: 10.3171/2019.4.jns19347
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of caudate deep brain stimulation for treatment-resistant tinnitus

Abstract: OBJECTIVEThe objective of this open-label, nonrandomized trial was to evaluate the efficacy and safety of bilateral caudate nucleus deep brain stimulation (DBS) for treatment-resistant tinnitus.METHODSSix participants underwent DBS electrode implantation. One participant was removed from the study for suicidality unrelated to brain stimulation. Participants underwent a stimulation optimization period that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…A recent phase I trial of caudate DBS for treatment-resistant tinnitus produced very encouraging results, and so this approach warrants further investigation. 85 …”
Section: Treatmentsmentioning
confidence: 99%
“…A recent phase I trial of caudate DBS for treatment-resistant tinnitus produced very encouraging results, and so this approach warrants further investigation. 85 …”
Section: Treatmentsmentioning
confidence: 99%
“…As this is a pilot study, no formal sample size calculation was performed. Based on previous rst-in-human DBS studies (43,56,57), we expect to adequately address the safety and the proof of concept purpose of the study by including six patients. Furthermore, this number of patients will enable collection of preliminary results that will provide meaningful information about differences between the intervention and sham stimulation.…”
Section: Sample Sizementioning
confidence: 99%
“…4 There are three major neurophysiological theories of chronic tinnitus that have inspired translational development of brain-based (cortical and subcortical) neuromodulation treatments. [5][6][7][8][9][10][11][12][13] The first theory posits mismatch between what the brain predicts it should be hearing and what sounds are actually delivered to the brain. 14,15 Expectation mismatch triggers auditory attention by subcortical neuromodulatory systems, manifesting clinically as tinnitus awareness.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Central to this theory is the critical role of the caudate nucleus of the striatum in phantom percept gate control. 6,20 Inconsistent replication of reported neuroanatomical alterations in chronic tinnitus across a multitude of studies has precluded the emergence of generally accepted features. In 2006, Mühlau et al 22 published one of the first tinnitus neuroanatomical studies and found decreased volume in the ventromedial prefrontal cortex of the limbic network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation